Transforming youth mental health: a Canadian perspective. (26th February 2015) - Iyer, S. N.; Boksa, P.; Lal, S.; Shah, J.; Marandola, G.; Jordan, G.; Doyle, M.; Joober, R.; Malla, A. K.
Abstract : In most mental illnesses, onset occurs before the age of 25 and the earliest stages are critical. The youth bear a large share of the burden of disease associated with mental illnesses. Yet, Canadian youths with mental health difficulties face delayed detection; long waiting lists; inaccessible, unengaging services; abrupt transitions between services; and, especially in remoter regions, even a complete lack of services. Responding to this crisis, the Canadian Institutes of Health Research announced a 5-year grant that was awarded to ACCESS, a pan-Canadian network of youths, families, clinicians, researchers, policymakers, community organisations and Indigenous communities. Using strategies developed collaboratively by all stakeholders, ACCESS will execute a youth mental healthcare transformation via early detection, rapid access and appropriate, high-quality care. The project includes an innovative, mixed-methods service research component. Similar in many respects to other national youth mental health initiatives, ACCESS also exhibits important differences of scale, scope and approach.